Impossible Origins: Trauma Narrative and Cinematic Adaptation - Linda Belau (Arts, 2021)
In this essay, I explore the cinematic adaptation and the representation of trauma, while I further consider the role and significance of the notion of the origin in both trauma and in cinematic adaptation. Through an initial consideration of the relationship between the theory of the impossible origin, particularly as it is articulated by Walter Benjamin, the essay goes on to analyze the significance and role of an impossible origin in the elemental form of adaptation. To this end, the essay considers the movement of adaptation from an autobiographical trauma memoir to a feature film, considering the success or failure of adaptation in situations where the original literary work concerns an experience of extremity. As I consider the vicissitudes of trauma and its grounding in a repetitious structure that leaves the survivor suspended in a kind of missed experience (or missed origin), I further explore how this missing origin (or original text in the case of adaptation) can be represented at all.